2018
DOI: 10.1002/gps.4992
|View full text |Cite
|
Sign up to set email alerts
|

Day care vs home care: Effects on functional health outcomes among long‐term care beneficiaries with dementia in Korea

Abstract: Objectives First, to compare changes in cognitive function, behavioral symptoms, and physical function for Korean Long‐Term Care Insurance (LTCI) beneficiaries with dementia in day care (DC) and home care (HC) settings over 1 year. Second, to examine the association between LTCI service type and the aforementioned health outcomes. Methods A retrospective matched cohort study was conducted using the national data set of the National Health Insurance Service in Korea. We identified 7822 beneficiaries with dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…This allows for determination of a causal relevance of health status and medical care utilization to be more representative [18]. There are studies analyzing the effectiveness of LTC systems using nationally-established datasets [21][22][23]. These results could provide an empirical basis for specific adjustments to policies and resource allocation.…”
Section: The Significance Of the Long-term Care Dataset And Previous mentioning
confidence: 99%
“…This allows for determination of a causal relevance of health status and medical care utilization to be more representative [18]. There are studies analyzing the effectiveness of LTC systems using nationally-established datasets [21][22][23]. These results could provide an empirical basis for specific adjustments to policies and resource allocation.…”
Section: The Significance Of the Long-term Care Dataset And Previous mentioning
confidence: 99%
“… 17 Lee et al compared the changes in cognitive function, behavioral symptoms, and physical function of Korean LTCI care and individual care in 1 year and found that the elderly experienced less cognitive decline and decreased disability progression in LTCI care. 18 Milte et al found a strong association between processes of care delivery and quality of life of care recipients. 19 All the theoretical research is becoming more and more in-depth, which were conducted from the perspectives of different age groups, nursing time, and health recovery degree, etc.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the hazard ratio of participant death of those using long-term care services was significantly lower than for those who did not use these services. Lee et al (2019) 18 Int J Geriatr Psychiatry Korea Logistic regression 2008–2009 The propensity score matching method was used, yielding 416 participants in each group. Paired samples t‐tests and logistic regression analyses were conducted and found that cognitive function and disability declined less in the LTCI care group.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fact that longer use of daycare services delays entry into care facilities or residential care hospitals ( Lee, 2006 ) also suggests that there is a need to improve older adults’ satisfaction with daycare services. For the care of older adults with dementia, cognitive function declined less in the daycare group than in the homecare group; however, conversely, behavioral symptoms showed a similar decrease between the two groups ( Lee et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%